Development of high-throughput multiplex serology to detect serum antibodies against Coxiella burnetii - Jeske, Rima; Dangel, Larissa; Sauerbrey, Leander; Frangoulidis, Dimitrios; Teras, Lauren R.; Fischer, Silke F.; Waterboer, Tim (Microorganisms, 2021)
The causative agent of Q fever, the bacterium Coxiella burnetii (C. burnetii), has gained increasing interest due to outbreak events and reports about it being a potential risk factor for the development of lymphomas. In order to conduct large-scale studies for population monitoring and to investigate possible associations more closely, accurate and cost-effective high-throughput assays are highly desired. To address this need, nine C. burnetii proteins were expressed as recombinant antigens for multiplex serology. This technique enables the quantitative high-throughput detection of antibodies to multiple antigens simultaneously in a single reaction. Based on a reference group of 76 seropositive and 91 seronegative sera, three antigens were able to detect C. burnetii infections. Com1, GroEL, and DnaK achieved specificities of 93%, 69%, and 77% and sensitivities of 64%, 72%, and 47%, respectively. Double positivity to Com1 and GroEL led to a combined specificity of 90% and a sensitivity of 71%. In a subgroup of seropositives with an increased risk for chronic Q fever, the double positivity to these markers reached a specificity of 90% and a sensitivity of 86%. Multiplex serology enables the detection of antibodies against C. burnetii and appears well-suited to investigate associations between C. burnetii infections and the clinical manifestations in large-scale studies.
Gesehen am 19.01.2022